The problematic of the history of feminist literature in the book "Women and Writing" by "Rashida Benmasoud", a critical study in "Beginnings". - م.د تحسين حسن جاسم (Journal of College of Education, 2023)
The Moroccan researcher "Rachida Benmasoud" has a great passion in exploring the nature of the literary production of Arab women, and the specificity of feminist writing. Questioning the heritage is one of her first procedures, as well as investigating the present from time in the Renaissance era to today, about women's contributions and their ability to crystallize the eloquence of difference in the vision of the world. Overlapping topics, and monitoring the foundations of variation and difference, in analyzing texts after selecting them. The research deals with the first section of the book titled "Beginnings", as the researcher presents the presence of women's contributions, and the biases of culture at the time, from the pre-Islamic era to the Renaissance, and perhaps more than one justification is explained by the research in choosing this part of the book; To monitor women's awareness in reading heritage, and their feminine critical sensitivity in monitoring the disguised hegemony in news formats that deal with women's contributions. The book is considered a source of feminist studies from a researcher who dedicated all her scientific output to women's issues, drawing on a number of knowledge from her studies at the Sorbonne, and from practical practice in political and legislative affairs when she was a member of the Moroccan Parliament (2002-2007) and as a founding member of the Center for Studies and Research on Women (Faculty of Arts - Dahr Al-Mahraz Fez) and a member of the central office of the Union of Moroccan Writers, and a member of the National Bureau of the Moroccan Organization for Human Rights, and president of the Women's Creativity Association..